Penerapan Distribusi Poisson Bivariat pada Data Jumlah Gol Hasil Pertandingan Sepak Bola Liga 1 Indonesia Tahun 2018-2019 - Alfan Siam Nuri; Aceng Komarudin Mutaqin (Bandung Conference Series: Statistics, 2023)
Abstract. On every continent in the world there are several prestigious league competitions that roll on and become a place to meet the best players, for example on the continent of Europe there are some of the best leagues. For example the English Premiere League (EPL) in England, La Liga in Spain, Serie A in Italy, the Bundes League in Germany and Ligue 1 in France. In Indonesia itself there is a league competition which is currently known as the Indonesian Super League (ISL) or the Indonesian League 1 which is the highest caste football competition between clubs in Indonesia which is participated in by 18 teams. There are several univariate and bivariate distributions that can be used to model data on the number of goals scored by football teams. One such bivariate distribution is the bivariate Poisson distribution. The maximum likelihood estimator method is used to estimate the parameters of the discrete distribution. While the distribution fit test to be used is the chi-square test. The data that will be used contains information on the number of goals for the home team and the number of goals for the away team in the 2018-2019 Indonesian Super League matches. The results of the application show that the bivariate Poisson distribution is suitable for modeling bivariate data on the number of goals for the home team and the away team for the 2018-2019 Indonesian Super League. Abstrak. Di setiap benua di dunia terdapat beberapa kompetisi liga bergengsi yang bergulir dan menjadi ajang bertemu pemain-pemain terbaik, misalnya benua Eropa terdapat beberapa liga terbaik. Contohnya English Premiere League (EPL) di Inggris, La Liga di Spanyol, Serie A di Italia, Bundes Liga di Jerman dan Ligue 1 di Francis. Di Indonesia sendiri terdapat kompetisi liga yang pada saat ini dikenal dengan sebutan Indonesian Super League (ISL) atau Liga 1 Indonesia yang merupakan kompetisi sepak bola kasta tertinggi antar klub di Indonesia yang diikuti oleh 18 tim. Terdapat beberapa distribusi univariat dan bivariat yang dapat digunakan untuk memodelkan data jumlah gol tim sepakbola. Salah satu distribusi bivariat tersebut adalah distribusi Poisson bivariat. Metode penaksir kemungkinan maksimum digunakan untuk menaksir parameter distribusi diskrit tersebut. Sedangkan uji kecocokan distribusi yang akan digunakan adalah uji chi-kuadrat. Data yang akan digunakan tersebut berisi informasi jumlah gol tim kandang dan jumlah gol tim tandang pertandingan Liga 1 Indonesia tahun 2018-2019. Hasil penerapan menunjukkan bahwa distribusi Poisson bivariat cocok untuk memodelkan data bivariat jumlah gol tim kandang dan tim tandang Liga 1 Indonesia tahun 2018-2019.